Development of Interactive Snakes and Ladders Media to Improve Student Learning Outcomes in Elementary School - Setyaningsih, Endah; Arini , Novanita Whindi (FKIP - Universitas Riau, 2025)
Students often struggle with understanding their rights and obligations in various contexts, which negatively impacts their learning outcomes. This study aimed to address this issue by developing an interactive snake and ladder game-based media tool that helps students grasp these concepts through engaging examples in daily life. The research employed the Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The interactive game was validated by media experts (96%), subject matter experts (98%), education practitioners (84%), and students. The overall validation score was 92%, qualifying it as